Principles of sedimentology and stratigraphy - Boggs, Sam; Boggs, Sam (New Jersey, Pearson Education, Inc., 2006)
A concise treatment of the fundamental principles of sedimentology and stratigraphy, featuring the important physical, chemical, biological and stratigraphic characteristics of sedimentary rocks. Emphasized are the ways in which the study of sedimentary rocks is used to interpret depositional environments, changes in ancient sea level, and other intriguing aspects of Earth history. Topics include the origin and transport of sedimentary materials; physical properties of sedimentary rocks; composition, classification and diagenesis of sedimentary rocks and principles of stratigraphy and basin analysis. For individuals interested in one text providing comprehensive coverage of both sedimentology and stratigraphy.
Appendix 582-622p.
Keywords: Deposition; Sedimentation; Sedimentology; Stratigraphy; Geology